2011
DOI: 10.1371/journal.pone.0017551
|View full text |Cite
|
Sign up to set email alerts
|

Association of Gender with Clinical Expression, Quality of Life, Disability, and Depression and Anxiety in Patients with Systemic Sclerosis

Abstract: ObjectivesTo assess the association of gender with clinical expression, health-related quality of life (HRQoL), disability, and self-reported symptoms of depression and anxiety in patients with systemic sclerosis (SSc).MethodsSSc patients fulfilling the American College of Rheumatology and/or the Leroy and Medsger criteria were assessed for clinical symptoms, disability, HRQoL, self-reported symptoms of depression and anxiety by specific measurement scales.ResultsOverall, 381 SSc patients (62 males) were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
43
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 48 publications
(58 reference statements)
8
43
2
1
Order By: Relevance
“…In a study, Nguyen et al [27] found no association with gender concerning perceived health status, HR-QoL and reported global and location-specific disability were not found. In the same study, women also have more self-reported symptoms of anxiety, while men were free of self-reported symptoms of both anxiety and depression [27]. The authors [27] concluded that gender is not a major determinant of perceived disability and impaired HR-QoL in SSc, but functional and social issues should be considered as severe in both.…”
Section: Gendermentioning
confidence: 91%
See 4 more Smart Citations
“…In a study, Nguyen et al [27] found no association with gender concerning perceived health status, HR-QoL and reported global and location-specific disability were not found. In the same study, women also have more self-reported symptoms of anxiety, while men were free of self-reported symptoms of both anxiety and depression [27]. The authors [27] concluded that gender is not a major determinant of perceived disability and impaired HR-QoL in SSc, but functional and social issues should be considered as severe in both.…”
Section: Gendermentioning
confidence: 91%
“…Women more often exhibit arthralgias, calcinosis and lcSSc [27]. In a study, Nguyen et al [27] found no association with gender concerning perceived health status, HR-QoL and reported global and location-specific disability were not found. In the same study, women also have more self-reported symptoms of anxiety, while men were free of self-reported symptoms of both anxiety and depression [27].…”
Section: Gendermentioning
confidence: 95%
See 3 more Smart Citations